2008
DOI: 10.1063/1.2952595
|View full text |Cite
|
Sign up to set email alerts
|

High-order large-eddy simulation of flow over the “Ahmed body” car model

Abstract: The structure of the turbulent flow over a simplified automotive model, the Ahmed body (S. R. Ahmed and G. Ramm, SAE Paper No. 8403001, 1984) with a 25° slanted back face, is investigated using high-order large-eddy simulations (LESs) at Reynolds number Re=768000. The numerical approach is carried out with a multidomain spectral Chebyshev–Fourier solver and the bluff body is modeled with a pseudopenalization method. The LES capability is implemented thanks to a spectral vanishing viscosity (SVV) technique, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 29 publications
4
99
0
Order By: Relevance
“…The Ahmed body and rear spoiler is enclosed in a computational domain of size 8L × 5H × 5W in the streamwise, transverse and spanwise directions, respectively (where L = length, H = height and W = width of the Ahmed body). The size of the computational domain is consistent with the previous studies (see for example, [18][19][20]), where the blockage effects are minimized. The standard dimensions for the Ahmed body with the rear slant angle  = 35 o were used, as shown in Figure 1(b), which may be found in [17,18].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The Ahmed body and rear spoiler is enclosed in a computational domain of size 8L × 5H × 5W in the streamwise, transverse and spanwise directions, respectively (where L = length, H = height and W = width of the Ahmed body). The size of the computational domain is consistent with the previous studies (see for example, [18][19][20]), where the blockage effects are minimized. The standard dimensions for the Ahmed body with the rear slant angle  = 35 o were used, as shown in Figure 1(b), which may be found in [17,18].…”
Section: Introductionsupporting
confidence: 74%
“…In order to model the flow and to facilitate the fluid grid movement as the fluid boundary changes with the interfacing rear spoiler motion, the unsteady ReynoldsAveraged Navier-Stokes (RANS) equation is solved together with the conservation of mass, in an Arbitrary Lagrangian-Eulerian description [21]. Previous studies have shown that RANS-based models are still appropriate in comparison with the experimental results, for a rear slant angle of 35 o [20]. In the present study, we employ a k- SST (shear stress transport) turbulence model in order to simulate the turbulent flow.…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent unified hybrid approach is Detached Eddy Simulation (DES) proposed by Spalart et al [39]. Indeed, the DES of Menter and Kuntz [29,30] and Kapadia et al [20] show globally much better results than the ones provided by RANS approaches. They resolve in particular for u = 25°the vortical structures in the wake as well as in the shear layer between the freestream and the recirculation but do not recover the partial detachment on the slant.…”
Section: Computational Grid and Boundary Conditionsmentioning
confidence: 99%
“…More recently, a number of LES & DES studies have been performed on this case, mainly at the more challenging 25 o slant angle [22,28,29,30,26,31,32,27,19]. These studies were performed with a range of sub-grid scale models and wall-treatments and, while some were more successful than others, many failed to capture fully the correct recirculation region.…”
Section: Ahmed Car Bodymentioning
confidence: 99%
See 1 more Smart Citation